Prospek Pengembangan Usaha Pada UMK Pengupasan Daging Rajungan Di Sei Ladi Kota Tanjungpinang - Lasari, Yosi; Khairunnisa, Khairunnisa; Tetty, Tetty (Department of Socio-economic Fisheries, Marine Science and Fisheries Faculty, Universitas Maritim Raja Ali Haji, 2021)
This study aimed to analyze the feasibility business of UMK Pengupasan Daging Rajungan. This research was in February-April 2021 in UMK Pengupasan Daging Rajungan Sei Ladi of Tanjungpinang city. The sampling method used is the purposive sampling method. The feasibility was analyzed using R/C ratio, B/C Ratio, BEP Volume, BEP Price, Payback Period, and NPV. Business development prospect in UMK Pengupasan Daging Rajungan will be identified using a SWOT analysis. The research result obtained profit for UMK Pengupasan Daging Rajungan, the R/C Ratio value is 2.45, B/C Ratio is 1,45, BEP Volume is 4.718.22 kg, BEP is Rp101.985, Payback Period is 1 year, 2 months 7 days, NPV is Rp5.713.143.210. UMK Pengupasan Daging Rajungan is profitable and feasible to be developed. Based on the identified SWOT analysis, UMK Pengupasan Daging Rajungan has 6 advantages in terms of capital, complete infrastructure, strategic location, carrying out fishing development, empowering marine products, and already having a business license. Weaknesses of UMK Pengupasan Daging Rajungan unstable crab supply and the absence of utilization of crab shell waste. Opportunities owned by UMK Pengupasan Daging Rajungan are a large market, the opportunity to expand their business, high market demand, and having regular customers. Meanwhile, the current threats are the lack of fishing gear, competitors, Pandemic Covid-19, and the used fishing gear that damages the crab habitats.